Assessing the appropriateness of the management of upper respiratory tract infection in Australian children: a population-based sample survey. Issue 5 (14th May 2019) - Long, Janet C; Williams, Helena M; Jani, Shefali; Arnolda, Gaston; Ting, Hsuen P; Molloy, Charlotte J; Hibbert, Peter D; Churruca, Kate; Ellis, Louise A; Braithwaite, Jeffrey
Abstract : Objective: To assess the proportion of Australian children aged 0–15 years that received care in line with clinical practice guidelines (CPGs) for upper respiratory tract infections (URTIs). Design: Retrospective medical record review using a multistage sampling strategy. Setting: General practices, hospital emergency departments and hospital inpatient service providers in three Australian states. Participants: Children aged up to 15 years who received care for URTI in 2012 and 2013. Primary and secondary outcome measures: The primary assessment was estimated adherence with 14 indicators of appropriate care as documented in medical records. Indicators were extracted from national and international CPGs and ratified by experts. Secondary assessment was adherence to two bundles of indicators (diagnostic symptoms and medical history taking), where all indicators must be adherent for the bundle to be scored as adherent. Results: There were 1653 children with one or more assessments of URTI care to CPG adherence. Over half of the children were under 3 years of age, with roughly equal numbers of males and females. Three indicators had fewer than 25 visits so were not reported. Overall adherence ranged from 0.5% for 'documented advice around antibiotics' to 88.3% for 'documentation of medical history'. Adherence with Bundle A (documentation of all three definitive symptoms) was 43.1% (95% CI 32.8% to 54.0%) and Bundle B (documentation of all four indicators of medical history) was 30.2% (95% CI 20.9% to 40.9%). Conclusions: URTIs in children are common, usually self-limiting, conditions that are allocated considerable resources. The results suggest that there may be a need for more thorough holistic assessment of the patient and improved documentation. Since inappropriate prescription of antibiotics for URTIs is still a known problem in Australia, there is a need for consistent, clear communication around antibiotics' lack of impact on symptoms and a high association with undesirable side effects.